Invited Speaker for the Global Learning System GLS and Sharing Knowledge Program at the BINUS University, Indonesia - Yuhani, Yusof (PSM, UMP, 2022)
Program of Modern Algebra and as a Sharing Knowledge Program to BINUS University, Indonesia on 17 November 2022. Through this valuable session, 126 participants comprising the School of Computer Science, BINUS University students, and colleagues interacted through the Zoom meeting platform on the Group of Permutation topic.